Asymmetries observed in Saturn's magnetopause geometry. Issue 17 (3rd September 2015) - Pilkington, N. M.; Achilleos, N.; Arridge, C. S.; Guio, P.; Masters, A.; Ray, L. C.; Sergis, N.; Thomsen, M. F.; Coates, A. J.; Dougherty, M. K.
Abstract For over 10 years, the Cassini spacecraft has patrolled Saturn's magnetosphere and observed its magnetopause boundary over a wide range of prevailing solar wind and interior plasma conditions. We now have data that enable us to resolve a significant dawn‐dusk asymmetry and find that the magnetosphere extends farther from the planet on the dawnside of the planet by 7 ± 1%. In addition, an opposing dawn‐dusk asymmetry in the suprathermal plasma pressure adjacent to the magnetopause has been observed. This probably acts to reduce the size asymmetry and may explain the discrepancy between the degree of asymmetry found here and a similar asymmetry found by Kivelson and Jia (2014) using MHD simulations. Finally, these observations sample a wide range of season, allowing the "intrinsic" polar flattening (14 ± 1%) caused by the magnetodisc to be separated from the seasonally induced north‐south asymmetry in the magnetopause shape found theoretically (5 ± 1% when the planet's magnetic dipole is tilted away from the Sun by 10–17°).